Requirement for endocytic antigen processing and influence of invariant chain and H-2M deficiencies in CNS autoimmunity. - Slavin, A; Soos, J; Stuve, O; Patarroyo, J; Weiner, H; Fontana, A; Bikoff, E; Zamvil, S (2001)
The role of processing in antigen (Ag) presentation and T cell activation in experimental allergic encephalomyelitis (EAE) was evaluated in wild-type mice, mice that selectively express either Ii p31 or p41, and mice completely deficient in Ii or H-2M. We demonstrate that processing of myelin oligodendrocyte glycoprotein (MOG) is required for presentation of the dominant encephalitogenic MOG epitope, p35-55. Ii p31- and p41-expressing mice developed EAE with similar incidence to wild-type mice, although p41 mice had a more severe course. Ag-presenting cells (APCs) from Ii- or H-2M-deficient mice could present p35-55, but not MOG, demonstrating that these APCs could not process native MOG. Ii- and H-2M-deficient mice were not susceptible to EAE by immunization with p35-55 or MOG or by adoptive transfer of encephalitogenic T cells. However, CD4+ T cells from p35-55-immunized H-2M-deficient mice proliferated, secreted IFN-gamma, and transferred EAE to wild-type, but not H-2M-deficient, mice. Thus, EAE resistance in H-2M-deficient mice is not due to an inability of APCs to present p35-55, or an intrinsic defect in the encephalitogenic T cell repertoire, but reflects a defect in APC function. Our results indicate that processing is required for initial Ag presentation and CNS T cell activation and suggest that autopathogenic peptides of CNS autoantigen may not be readily available for presentation without processing.